2003
DOI: 10.1179/cmq.2003.42.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution and Strength in Hot Working of ZK60 and other Mg Alloys

Abstract: The microstructures close to the gauge surface were observed by optical and transmission electron (TEM) microscopy in ZK60 (Mg-5.7Zn-0.65Zr) and in AZ31S (Mg-2.8Al-0.9Zn) after torsion testing over 180 -450 °C and 0.01 to 1.0 s -1 . The flow curves rose rapidly to a peak stress which was lower as temperature T rose and strain rate declined. At or below 240 °C, the stress fell rapidly to fracture but at or above 300 °C the curves descended less rapidly and extended into plateaus until failure. Clearly, grains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…These phenomena could be explained by the Zener-Hollomon parameter according to McQueen theory. 14,15 That is, the mean size of the recrystallised grain decreases with the decrease in temperature or the increase in Z parameter. found that the morphology and density of dislocation depends on both deformation temperatures and second phases related to basal and non-basal slip.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These phenomena could be explained by the Zener-Hollomon parameter according to McQueen theory. 14,15 That is, the mean size of the recrystallised grain decreases with the decrease in temperature or the increase in Z parameter. found that the morphology and density of dislocation depends on both deformation temperatures and second phases related to basal and non-basal slip.…”
Section: Resultsmentioning
confidence: 97%
“…These phenomena could be explained by the Zener-Hollomon parameter according to McQueen theory. 14,15 That is, the mean size of the recrystallised grain decreases with the decrease in temperature or the increase in Z parameter. Figure 5 shows TEM observation for the alloy of Mg-6Zn-2Nd-0?5Zr at different temperature.…”
Section: Microstructure Changing During Hot Deformationmentioning
confidence: 99%
“…With increasing temperature the contribution of the twinning to total deformation gradually decreases. Detailed deformation twinning was reported by several researchers (Ref [31][32][33][34][35]. The twinning process not only accommodates a certain amount of shape change itself, but it also partially changes the crystallographic orientation and thus regenerates favorable basal slip system.…”
Section: Creep Of Magnesium Alloysmentioning
confidence: 97%
“…Moreover, different kinds of thermomechanical processing (TMP) may lead to different DRX phenomena, such as discontinuous DRX (DDRX), continuous DRX (CDRX), and geometric DRX (GDRX) [ 20 ]. In order to recognize the differences of the three DRX types, many efforts [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] have been made on the observation and revelation of microstructural evolution during the hot forming process. DDRX usually occurs with new strain-free grains nucleation and the grains growth in low-stacking-fault energy (SFE) metals and alloys [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the mechanisms above, two numerical models of CDRX, the Gourdet-Montheillet model [ 33 ] and Toth et al model [ 34 ], are proposed to characterize this process. Apart from DDRX and CDRX, GDRX is a field with less study, but is still observed in some metals and alloys during a large amount of hot deformation, such as commercial-purity Al [ 35 ] and Mg–Zn–Zr alloys [ 36 , 37 ]. However, the microstructural evolution with constitutive analysis for 2219 Al alloy under the hot deformation process is rarely reported.…”
Section: Introductionmentioning
confidence: 99%